Mitigative Practices for Ammonia Gas Emissions from Poultry Manure - Serkan Yazarel; Şenay Sarıca; Sedat Karaman (Turkish Journal of Agriculture: Food Science and Technology, 2020)
Proteins consumed by poultry turns into ammonia as a result of microbial activities depending on the pH, temperature, moisture content of the litter, litter type, manure condition, relative humidity and ventilation condition and spreads to the environment as ammonia gas. Ammonia gas, which is one of the problems caused by poultry breeding, is a harmful gas in terms of animal welfare, health of employees and its effects on the environment. In this article, ammonia gas emission in poultry and practices to reduce this emission have been discussed and recommendations have been made.